Bilateral rupture of the posterior capsule and intraocular lens dislocation from excessive eye rubbing. Issue 2 (February 2016) - Bassily, Ramy; Lencova, Anna; Rajan, Madhavan S.
Abstract : N/A: We report an unusual case of a 36‐year‐old woman with severe atopic eczema who developed sudden‐onset reduction of vision in the right eye following excessive eye rubbing 9 years after cataract surgery. Examination identified posterior capsule rupture with dislocation of the intraocular lens (IOL) posteriorly into the vitreous cavity in the right eye and posterior capsule rupture with mild dislocation of the IOL in the bag in the left eye. To our knowledge, this is the first reported case of simultaneous bilateral posterior capsule rupture following uneventful surgery and secondary to eye rubbing. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.